Draconema: A remarkable genus of marine free-living nematodes. - Cobb, N. A. (J. Wash. Acad. Sci., 1913)
Locality: Kingston Harbor, Port Royal, Jamaica; Cabinet:
Locality: Kingston Harbor, Port Royal, Jamaica; Cabinet:; NeMys doc_id: 4657